'We do not Want any more masters': ruins, planning and the " messy labours " of the urban poor - (:unkn) unknown (My University, 2016)
The article demonstrate how some parts of Nairobi city have been neglected for along time despite having been integratedin the City Master Plan. There is an indication that, most part of Eastern Nairobi such as Mathare, Kosovo settlements have been marginalized by city planners.
Keywords: African Research